Komparasi Efikasi Skrining Kanker Serviks Menggunakan HPV DNA Testing, Pap Smear, Dan Liquid Biopsy: Tinjauan Sistematis - Mayasari, Septia Puji (Indonesian Journal of Health Community, 2025)
Cervical cancer is one of the leading causes of death among women worldwide, making early detection through effective screening crucial. This study aims to compare the efficacy of three cervical cancer screening methods: HPV DNA testing, pap smear, and liquid biopsy. The method used is a systematic review based on the PRISMA 2020 guidelines, with literature searches conducted in PubMed, Scopus, ScienceDirect, and Google Scholar from 2019 to 2025. Out of 657 articles, 17 studies met the inclusion criteria and were analyzed descriptively and comparatively. The results indicated that HPV DNA testing had the highest sensitivity (73–96%) and negative predictive value (90–99%), but its specificity varied (39–97%). Pap smear had lower sensitivity (30–64%) but good specificity and positive predictive value (65–92% and 63–89%). Liquid biopsy offered very high specificity and positive predictive value (89–100% and 70–100%), but its sensitivity was still limited (27–78%). A combination of the three methods is recommended to improve diagnostic accuracy and the effectiveness of cervical cancer screening. HPV DNA testing excels in early detection, Pap smear is suitable for resource-limited areas, and liquid biopsy holds potential as a confirmation or monitoring method.